Effect of Weed Management Practices on Nutrient Uptake and Economics of Mustard (Brassica juncea) - Y. Yernaidu; Y. S. Parameswari; M. Madhavi; T. Ramprakash (International Journal of Economic Plants)
A field experiment was conducted during rabi season (November to February, 2020–21) at College Farm, College of Agriculture, Rajendranagar, Hyderabad. The farm is geographically positioned at 17°19’16.4” North latitude and 78°24’43” East longitude and at an altitude of 542.3 m above the mean sea level. According to troll’s climatic classification, it is categorized under semi-arid tropics (SAT). The experimental field was sandy loam texture with available nitrogen (223 kg ha-1), available phosphorus (30.87 kg ha-1) and potassium (375.72 kg ha-1). Mustard variety NRCHB-101 was sown with seed rate of 4 kg ha-1. The seeds were sown in solid rows 40 cm apart between rows and at a depth of 3‒4 cm and covered with loose soil immediately after seeding.  The experiment was laid out in randomized block design with twelve treatments and replicated thrice. The data was analyzed using standard statistical techniques. Among different weed management practices, higher nutrient uptake (59.57, 24.51, 52.46 kg ha-1 ) by crop were observed under intercultivation and hand weeding at 15 and 30 DAS and it was on par with Oxadiargyl 6% EC 0.09 kg ha-1 PE fb intercultivation at 30 DAS.  Similarly higher gross and net returns (68933/- and 42952/-) were noticed with intercultivation and hand weeding at 15 and 30 DAS and it was on par with Oxadiargyl 6% EC 0.09 kg ha- 1PE fb intercultivation at 30 DAS. Higher B:C ratio was noticed under Oxadiargyl 6% EC 0.09 kg ha-1 PE fb intercultivation at 30 DAS (2.96).